Pengaruh Penggunaan Tiktok Shop Dan Perilaku Keuangan Terhadap Keputusan Pembelian Produk Kecantikan Pada Generasi Z Di Desa Mendalo Indah - Tiara Gunita; Hansen Rusliani; Solichah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the influence of TikTok Shop usage and financial behavior on beauty product purchasing decisions among Generation Z in Mendalo Indah Village, Muaro Jambi Regency. The study is motivated by the increasing use of social media as an online shopping platform and the high interest of Generation Z in beauty products promoted through TikTok Shop. In addition to the external factor of TikTok Shop usage, financial behavior is considered an internal factor influencing consumer purchasing decisions. This research employed a quantitative approach with an associative research design. The population consisted of Generation Z individuals residing in Mendalo Indah Village who had purchased beauty products through TikTok Shop. A total of 100 respondents were selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software.The results indicate that TikTok Shop usage has a positive and significant effect on beauty product purchasing decisions among Generation Z in Mendalo Indah Village. Features such as live shopping, promotional videos, customer reviews, and discount programs have been proven to increase consumer interest and purchasing decisions. Financial behavior also has a positive and significant effect on purchasing decisions. Generation Z consumers with better financial behavior tend to be more rational in considering their needs, product benefits, and financial capabilities before making purchases. Simultaneously, TikTok Shop usage and financial behavior significantly influence beauty product purchasing decisions. These findings suggest that purchasing decisions are shaped by the interaction between external and internal factors. Therefore, business actors should optimize digital marketing strategies through TikTok Shop, while consumers should improve their financial management skills to make wiser purchasing decisions.